OMG... we're in a horror movie! - Bandele, Ajala; Hatfield, Tom (Screenwriter); McGowan, Brendan (Actor); Wang, Sharon Mae; Alchemical Brothers (Firm); Leomark Studios (Firm) ([United States] : Alchemical Brothers, 2016)
Six friends having a weekly board game night are interrupted by a booming movie trailer voice from the sky. Inexplicably, they find themselves trapped in a Horror Movie. Who amongst them will turn into a homicidal killer? Who will be the sole survivor? And who will be the first to die in the shower? Struggling to break free from the stereotypes that would see them dead, each of the friends try to stay alive in whatever hopelessly desperate ways they can.
Originally released as a motion picture in 2016
Brendan McGowan, Sharon Mae Wang, Nils Jansson, Shanna Malcolm, Chris Hampton, Ajala Bandele, Liz Fenning.
Cinematographer, Greg Loebell ; editor, Ajala Bandele ; original score by Tyler David Gilbert ; original songs by Tom Hatfield.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 1, 2017).
Keywords: Horror films; Comedy films; Feature films; Internet videos; Streaming video